Electricity, Exergy and Economic Growth in Mozambique - Huo, Teles; St. Aubyn, Miguel (International Journal of Energy Economics and Policy, 2022)
Electricity consumption and economic growth attracted the attention of researchers in several countries. Mozambique have few studies on this matter and non-related to useful exergy. This paper analyses the relationship between final electricity consumption, useful exergy and economic growth in Mozambique, from 1971 to 2014. The final electricity consumption data are expressed in GWh, from International Energy Agency database, which for Mozambique (until the date of writing) cover the period from 1971 to 2014. For this analysis an unrestricted VAR models were estimated to capture different types of effects, which are particularly important for an economy that underwent diverse phases and restructuring processes. Results indicate that there was a huge increase in final electricity consumption, from 2000 and 2001. Modelling with final electricity consumption and with useful energy illustrated that economic growth in Mozambique has not been influenced by final electricity consumption and useful exergy. However, economic growth induces final electricity consumption and useful exergy growth. The results suggests that sectors that induce economic growth in Mozambique are the least electricity intensive ones. The Police implications is that electricity access of those sectors that induce economic growth should be enhanced to keep them more competitive, and to sustain the growth.